Characterization of calcium- and integrin-binding protein 1 (CIB1) knockout platelets: Potential compensation by CIB family members - DeNofrio, Jan C.; Yuan, Weiping; Temple, Brenda R.; Gentry, Holly R.; Parise, Leslie V. (Thrombosis and Haemostasis, 2008)
Platelet aggregation requires activation of the αIIbβ3 integrin,an event regulated by the integrin cytoplasmic tails. CIB1 binds to the cytoplasmic tail of the integrin αIIb subunit. Previous overexpression and knockdown studies in murine megakaryocytes demonstrated that CIB1 inhibits integrin αIIbβ3 activation.Here we analyzed Cib1-/- mice to determine the function of CIB1 in platelets in vitro and in vivo. We found that although these mice had no overt platelet phenotype, mRNA level of CIB1 homolog CIB3 was increased in Cib1-/- megakaryocytes. In vitro binding experiments showed that recombinant CIB1, -2 and -3 bound specifically to an αIIb cytoplasmic tail peptide. Subsequent protein modeling experiments indicated that CIBs 1–3 each have a highly conserved hydrophobic binding pocket. Therefore, the potential exists for compensation for the loss of CIB1 by these CIB family members, thereby preventing pathologic thrombus formation in Cib1-/- mice.
Keywords: CIB1; platelet; integrin αIIbβ3 activation; aggregation; knockout mouse; compensation